Pengaruh Senam Kaki terhadap Penurunan Skor Neuropati dan Kadar Gula Darah pada Pasien DM Tipe 2 di Persadia RS. TK. II. Dustira Cimahi - Rita Fitri Yulita; Agung Waluyo; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of foot exercise on the reduction of neuropathy scores and blood sugar levels in type 2 DM patients. This study used a quasi experimental design with a pretest-posttest control group design approach. The results of the study in the intervention group there was a significant decrease in neuropathy scores and blood sugar levels (p = 0.001). While in the control group there was no significant decrease in neuropathy scores (p = 0.069) and blood sugar levels (p = 0.184). Based on the results of the Mann-Withney test, it showed that there was a significant difference in decreasing neuropathy scores and blood sugar levels between the intervention group and the control group (p = 0.003; p = 0.042). In conclusion, patients with type 2 diabetes mellitus who were given foot exercises experienced a decrease in neuropathy scores and blood sugar levels. Keywords: Type 2 DM, MNSI Instrument, Blood Sugar Levels, Foot Exercise, Neuropathy Score